2014
DOI: 10.3390/w6071985
|View full text |Cite
|
Sign up to set email alerts
|

Water End-Uses in Low-Income Houses in Southern Brazil

Abstract: Knowing water consumption patterns in buildings is key information for water planning. This article aims to characterize the water consumption pattern and water end-uses in low-income houses in the region of Florianópolis, Southern Brazil. Data were collected by interviewing householders, as well as by measuring the flow rate of existing water fixtures and appliances. The results indicated that the shower was the fixture with the largest water consumption in households, i.e., about 30%-36% of total water consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 10 publications
0
23
0
6
Order By: Relevance
“…Only 24% of the studies reviewed by Worthington and Hoffmann [15] related to Europe. Although studies from the US have remained common since 2006 [17,18], many have also concentrated on developing countries ( [19] and references therein), for example, Marinoski et al [20] focused on Brazil and Araral and Wang [21] focused on key cities, states, and/or provinces in Southeast Asia. In addition, many European countries have featured in recent studies concerned with water consumption (Table 1), including France [22,23], Cyprus [24], Spain [25][26][27][28][29], Sweden [30,31], Germany [32], Denmark [33], Greece [34], and Poland [35].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 24% of the studies reviewed by Worthington and Hoffmann [15] related to Europe. Although studies from the US have remained common since 2006 [17,18], many have also concentrated on developing countries ( [19] and references therein), for example, Marinoski et al [20] focused on Brazil and Araral and Wang [21] focused on key cities, states, and/or provinces in Southeast Asia. In addition, many European countries have featured in recent studies concerned with water consumption (Table 1), including France [22,23], Cyprus [24], Spain [25][26][27][28][29], Sweden [30,31], Germany [32], Denmark [33], Greece [34], and Poland [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Exploring the determinants of water consumption requires the consideration of tariffs and income, but also many other factors, such as population characteristics [12,25,29,32,36,37], population density [38], the presence of immigrants [29] or tourists [12][13][14][15][16][17][18][19][20][21][22][23][24][25], and household features [10,12,[26][27][28][29]31,32,35,37,39], or house characteristics [12,22,28,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study is important because, besides obtaining water end-uses in the flats, it also investigates the perception of residents related to rainwater harvesting, which has been little explored in the scientific literature.Water 2020, 12, 546 2 of 22 the potential for potable water savings through the use of rainwater occur due to different demands for potable water and different rainwater catchment areas. Research conducted in public buildings in Florianópolis showed that between 56% and 86% of the potable water consumption could be replaced with rainwater [12,13].Regarding the water end-uses in residential buildings in different countries, it is noticeable that, in general, showers contribute to the highest water consumption [14][15][16][17][18][19]. Beyond that, the percentage of water consumed for toilet flushes is significant.…”
mentioning
confidence: 99%
“…Regarding the water end-uses in residential buildings in different countries, it is noticeable that, in general, showers contribute to the highest water consumption [14][15][16][17][18][19]. Beyond that, the percentage of water consumed for toilet flushes is significant.…”
mentioning
confidence: 99%
“…The potential for potable water savings is closely related to the water end-uses. Thus, some researchers have been developing research on the water end-uses in residential buildings [56,[72][73][74][75][76][77][78][79], schools [80,81], hotels [82], office buildings [83] and public administrative buildings [84]. The average, minimum and maximum non-potable uses are shown in Figure 2.…”
Section: Potential For Potable Water Savingsmentioning
confidence: 99%